Review of Bleach Activators for Environmentally Efficient Bleaching of Textiles (Journal of Fiber Bioengineering and Informatics, 2018)
Textile wet processing is the most polluting aspect of textile manufacturing and contributes to the globaltextile industry's substantial carbon footprint. Textile preparation of cotton typically includes scouringand bleaching at high temperature and high pH. Substantial amounts of wastewater are produced thatmust be treated prior to being released to receiving fresh water. Recent research in our laboratorieshas focused on the development and application of compounds that enhance the bleaching process.We have developed novel cationic bleach activators that can be used to bleach cellulosic fabrics andfiber blends at reduced temperature, pH, and time. Results show that after optimization equivalentor improved performance in whiteness, absorbency and strength are possible relative to conventionalbleaching methods. One of the most promising bleach activators to date is N-[4-(Triethylammoniomethyl)Benzoyl]-Butyrolactam Chloride (TBBC). TBBC was designed in our group to a) exhibit strong oxidationpotential when activated; b) have reasonable hydrolytic stability; and c) be inherently substantivetowards cellulosic and other fibers. In this paper, we review the development of bleach activators fortextile bleaching, and discuss the opportunities and potential hurdles involved in commercialization ofbleach activators for textile wet processing.